Long-term rotation fertilisation has differential effects on soil phosphorus - Xue Li; Qiuxiang Wen; Shiyu Zhang; Na Li; Jinfeng Yang; Xiaori Han (Plant, Soil and Environment, 2020)
The application of organic fertiliser is a commonly used method to improve the utilisation efficiency of phosphorus (P) fertiliser. However, long-term over-fertilisation will cause environmental pollution. This study analysed a field test was conducted to study the impacts of P forms in soil under long-term (40 years) rotation fertilisation, to evaluate the contribution of different fertilisation to the available P form, to clarify how to apply pig manure to improve the concentration of available P forms. The results show that the main P compounds were orthophosphate and phosphate monoester. The combination of a high amount of manure and NPK fertilisers can increase the content of orthophosphate that can be absorbed and utilised by crops, the orthophosphate was 477.2 mg/kg, and phosphate monoester was 190.4 mg/kg. The long-term addition of nitrogen fertiliser significantly reduced the pH value of soil, and the addition of manure slowed down the trend of pH reduction. Furthermore, manure in combination with NPK fertiliser, can extremely increase the total P extracted by NaOH-EDTA by changing soil pH. The NaHCO3-soluble P (Ca2-P), NH4Ac-soluble P (Ca8-P), NH4F-soluble P (Al-P), and occluded-P (O-P) were positively correlated with orthophosphate, while middle stable and high stable organic P was positively correlated with monophosphate.